2017
DOI: 10.1080/17489725.2017.1333638
|View full text |Cite
|
Sign up to set email alerts
|

Extracting regular mobility patterns from sparse CDR data without a priori assumptions

Abstract: In this work we present two methods that can extract habitual movement patterns and reconstruct the underlying movement of users from their call detail records (CDR) in a way that works for users with only moderate numbers of CDRs and that does not make any prior assumptions on the behaviour of the users. The methods allow for a more comprehensive user base in large-scale studies due to the fact that users that might otherwise have to be discarded can also be analysed. The first one is computationally not over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The splitting of the raw data into trips is not part of this work, as the stays were for the most part very clearly discernible. This assumes long stays with short times of movement in between, as was already observed in other studies (Burkhard et al, 2017).…”
Section: Terminologymentioning
confidence: 64%
“…The splitting of the raw data into trips is not part of this work, as the stays were for the most part very clearly discernible. This assumes long stays with short times of movement in between, as was already observed in other studies (Burkhard et al, 2017).…”
Section: Terminologymentioning
confidence: 64%
“…Their study suggests that filling the gaps in the sparse individual traces results in better representation of travel demand, e.g., the truncated power-law distribution of trip distance distributions. Burkhard et al (2017) have reconstructed regular mobility patterns from users with sparse CDRs using idiosyncratic daily patterns from clustered daily activities [25].…”
Section: A Related Workmentioning
confidence: 99%
“…Often 1 week of GPS data are recorded to assess an individual's habitual movement, assuming that the majority of the movement patterns are repeated on a weekly basis (Cornwell & Cagney, 2017;Giannouli et al, 2016;Kestens et al, 2016;Schmidt, Kerr, Kestens, & Schipperijn, 2018). Some GPS studies have shown, however, that a minimum of 14 days of GPS data are needed to obtain a stable measure of an individual's activity space (Stanley, Yoo, Paul, & Bell, 2018;Zenk, Matthews, Kraft, & Jones, 2018) and people's movement habits may change to a greater extent than expected (Burkhard, Ahas, Saluveer, & Weibel, 2018).…”
Section: Movement: How People Are Mobilementioning
confidence: 99%